Numerical calculation of heat and mass transfer processes in the adsorbers of the air purification system - et. al., O.V. Tushavina, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this work, a series of parametric calculations was made for the processes of sorption and desorption of water vapor in relation to the conditions of the process of sorption air purification. A mathematical model was developed that adequately reflects the processes of heat and mass transfer in the adsorption unit at all stages of the adsorption cycle. Algorithms for solving problems and programs for calculating heat and mass transfer processes in an adsorption regenerated installation are obtained, results of parametric calculations of heat and mass transfer processes at each stage of the adsorption cycle and for the entire cycle as a whole are obtained.